REVISITING ISLAMIC ECONOMICS: BETWEEN IDEALISM AND PRACTICAL CHALLENGES - Sekar Nurhastuti (PT. Samudra Solusi Profesional, 2025)
Islamic economics has emerged as a prominent alternative framework to conventional economic systems, particularly in the aftermath of recurring global financial crises that have exposed structural weaknesses in interest-based, speculative, and debt-driven economic models. Rooted in Islamic ethical principles such as justice (ʿadl), welfare (maṣlaḥah), balance (tawāzun), and the prohibition of ribā, gharar, and maysir, Islamic economics aspires to construct an economic order that harmonizes material prosperity with moral responsibility. Despite its rapid institutional expansion especially through Islamic banking, finance, and halal industries significant debates persist regarding the extent to which contemporary practices genuinely reflect the foundational ideals of Islamic economic thought. This article revisits Islamic economics through a conceptual–critical lens, interrogating the growing gap between its normative ideals and practical implementation. Employing a qualitative conceptual analysis and narrative literature review, the study synthesizes classical Islamic economic thought, modern theoretical formulations, and contemporary empirical critiques from both global and Indonesian contexts. The findings reveal three interrelated challenges: the dominance of form-over-substance compliance in Islamic financial institutions, the marginalization of socio-economic justice objectives in favor of market competitiveness, and persistent epistemological tensions arising from the adaptation of conventional economic paradigms. By problematizing these issues, the article contributes to the discourse on Islamic economics by advocating a reorientation toward its ethical–social foundations without neglecting institutional realities. This revisiting is crucial not only for strengthening the academic coherence of Islamic economics but also for enhancing its transformative capacity in addressing real-world economic inequalities and development challenges. The article concludes that Islamic economics must evolve beyond symbolic differentiation toward substantive ethical integration if it is to fulfill its promise as a viable and credible alternative economic paradigm.